Pencegahan Dampak Bencana Dengan Mitigasi Melalui Pemetaan Kebencanaan Berbasis GIS - Zainal Munir; Fuadz Hasyim (STIKES Citra Delima Bangka Belitung, 2020)
The topography of Probolinggo Regency is located on a slope mountains stretching from West to East, namely Mount Semeru, Mount Argopuro, Mount Bromo and Mount Lamongan. Probolinggo Regency is located at an altitude of 0- 2500 m above sea level, so that the land in Probolinggo Regency is land volcanic which contains many minerals that come from volcanic explosions in the form of sand, stone and mud mixed with clay which has fertility levels high. The highest rainfall is in January and February, rainfall is 1,797.82 mm2, 89 rainy days, 169,616.65 ha outside the mainland area. Meanwhile, Social Services do not have UPT PSTW, health services include 6 hospitals, 33 health centers, 1320 Posyandu, 87 supporting health centers, 1 unit that handles Disasters and 6 universities. This research uses the Waterfall method, produces a GIS-based disaster mitigation mapping application, this application provides information to the Regional Disaster Management Agency (BPBD) of Probolinggo Regency on the location of the map of the area that is included in the red zone that is at risk of disaster.